2011
DOI: 10.1097/aco.0b013e328347f931
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and anesthesia for the pediatric patient undergoing radiation therapy

Abstract: In the vast majority of cases, total intravenous anesthesia or sedation using propofol ensures that the child remains immobile, whilst maintaining spontaneous respiration, an unobstructed airway, and cardiovascular stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 24 publications
0
28
0
5
Order By: Relevance
“…While radiation therapy is painless, children can experience considerable anxiety due to unfamiliar and potentially frightening radiation equipment [3]. Nevertheless, children must be made motionless using anesthesia or sedation during this short procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While radiation therapy is painless, children can experience considerable anxiety due to unfamiliar and potentially frightening radiation equipment [3]. Nevertheless, children must be made motionless using anesthesia or sedation during this short procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, children must be made motionless using anesthesia or sedation during this short procedure. Propofol, ketamine, midazolam, and general anesthesia with sevoflurane have been administered as anesthetics or sedatives to pediatric patients [345]. Adverse effects, including respiratory depression and excessive sedation, may necessitate endotracheal intubation [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Alcorn et al 14, we found an extensive use of vacuum cushions (> 62%) for thoracic, abdominal and pelvic treatments. Our survey did not disclose anesthesia practices, whereas anesthesia or sedation is often required in the very young to ensure complete immobility during radiotherapy (28).…”
Section: Studymentioning
confidence: 99%
“…Many departments prefer the use of a conscious sedative rather than full general anesthesia, which would require intubation. Propofol is often used due to its ease of administration and quick recovery in a majority of patients (McFadyen et al, 2011). Most children need only an oxygen mask, but a few will require a laryngeal mask airway (LMA) or nasal trumpet to maintain a good airway.…”
Section: Immobilization/anesthesiamentioning
confidence: 99%